Antioxidant and antihyperglycemic potential of methanolic extract of bark of mimusops elengi l. In mice. - G. P. Ganu,; Jadhav S. S.,; Deshpande A. D, (International Journal of Phytomedicine, 2010)
Ayurveda refers Mimusops elengi L. for the treatment of the diabetes. Considering the traditional claim of M. elengi in management of diabetes and the possible involvement of oxidative stress in pathogenesis of diabetes, the present study was aimed to evaluate the in vitro antioxidant and in vivo antihyperglycemic property of methanolic extract of bark of M. elengi (MEMeOH). In vitro antioxidant activity of MEMeOH was evaluated using reducing power assay, DPPH and hydroxyl radical scavenging assay. MEMeOH offered significant in vitro reducing power capacity and radical scavenging activity. In acute study in alloxan induced diabetes, MEMeOH exhibited significant (p< 0.001) antihyperglycemic effect. The onset of antihyperglycemic effect was observed at 2nd hr; peak activity was demonstrated at 6th hr. The antihyperglycemic effect of MEMeOH 400mg/kg, p.o. was persistent up to 24th hr after drug administration. MEMeOH produced significant (p < 0.01) reduction in elevated glucose levels in glucose loaded non diabetic animals. The onset of action in non diabetic oral glucose tolerance test was found to be at 60th min and peak activity was observed at 120th min after oral glucose load. MEMeOH demonstrated significant (p < 0.01) reduction in elevated glucose levels 2hr before glucose administration and 6 hr after glucose load in oral glucose tolerance test in diabetic animals. MEMeOH has demonstrated antihyperglycemic activity in diabetic as well as non diabetic glucose loaded mice. MEMeOH should be further explored against diabetes and related complications.